2014
DOI: 10.1073/pnas.1413582111
|View full text |Cite
|
Sign up to set email alerts
|

Aag-initiated base excision repair promotes ischemia reperfusion injury in liver, brain, and kidney

Abstract: Inflammation is accompanied by the release of highly reactive oxygen and nitrogen species (RONS) that damage DNA, among other cellular molecules. Base excision repair (BER) is initiated by DNA glycosylases and is crucial in repairing RONS-induced DNA damage; the alkyladenine DNA glycosylase (Aag/Mpg) excises several DNA base lesions induced by the inflammation-associated RONS release that accompanies ischemia reperfusion (I/R). Using mouse I/R models we demonstrate that Aag −/− mice are significantly protected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 61 publications
3
37
0
Order By: Relevance
“…Nevertheless, many previous studies show that there can be conditions of imbalanced BER, wherein downstream BER enzymes are unable to keep up with DNA glycosylases [4244]. This can lead to an increase in the overall levels of SSBs, which can be converted to DSBs if closely opposed or if encountered by a replication fork [4548]. Indeed the observation that influenza leads to an increase in the levels of single strand lesions in vitro (as measured by the alkaline comet assay, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, many previous studies show that there can be conditions of imbalanced BER, wherein downstream BER enzymes are unable to keep up with DNA glycosylases [4244]. This can lead to an increase in the overall levels of SSBs, which can be converted to DSBs if closely opposed or if encountered by a replication fork [4548]. Indeed the observation that influenza leads to an increase in the levels of single strand lesions in vitro (as measured by the alkaline comet assay, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies investigating tissues and organs such as the brain, heart, kidney and retina have demonstrated that numerous free radicals are produced during IRI, when the endogenous radical scavengers cannot function appropriately, leading to cell damage (1,2). Therefore, investigating effective drugs that alleviate IRI-induced functional liver damage, and improve the postoperative survival rate, has become a research hotspot in the field of hepatic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…PARP1 inhibition has been shown to be beneficial in inflammatory diseases, such as diabetes, asthma and atherosclerosis (Ebrahimkhani et al, 2014; Sperling et al, 2013), through a variety of means, including the regulation of transcription factors, cytokines, adhesion factors and inflammatory mediators (Cummings et al, 2014; Jia et al, 2014; Stampfer, 2006). NF-κB, an inflammation mediator, was determined as a target for PARP1 activity (Godyn et al, 2016).…”
Section: Dna Repair Defects In Admentioning
confidence: 99%